2016
DOI: 10.1007/s00394-016-1181-5
|View full text |Cite
|
Sign up to set email alerts
|

Oregano demonstrates distinct tumour-suppressive effects in the breast carcinoma model

Abstract: Our results demonstrate, for the first time, a distinct tumour-suppressive effect of oregano in the breast cancer model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 49 publications
10
50
0
Order By: Relevance
“…Our experiment remarkably showed the pro‐apoptotic activities of high‐dose CLOs —it was characterized by an increase in the expression of caspase‐3 and Bax/Bcl‐2 ratio in rat mammary carcinomas. We have found similar findings in our earlier experiments reporting the pro‐apoptotic effects of Chlorella pyrenoidosa, fruit peels and oregano using the same rodent model . In our parallel in vitro study, we have demonstrated the decrease in a viability of MCF‐7 cell lines by clove's ethanol extract.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our experiment remarkably showed the pro‐apoptotic activities of high‐dose CLOs —it was characterized by an increase in the expression of caspase‐3 and Bax/Bcl‐2 ratio in rat mammary carcinomas. We have found similar findings in our earlier experiments reporting the pro‐apoptotic effects of Chlorella pyrenoidosa, fruit peels and oregano using the same rodent model . In our parallel in vitro study, we have demonstrated the decrease in a viability of MCF‐7 cell lines by clove's ethanol extract.…”
Section: Discussionsupporting
confidence: 89%
“…It is questionable whether an isolated plant secondary metabolite has the similar anticancer activities as the whole‐plant‐based food containing the cocktail of phytochemicals . In this regard, our earlier animal studies (with the same model and similar dosages as in this study) clearly demonstrated significant anticancer effects of plant foods (chlorella, fruit peels, oregano) containing mixtures of different phytochemicals manifesting comprehensive mechanism of action in the model of NMU‐induced mammary carcinogenesis in rats . Chemopreventive effects of plant foods, concretely rosemary, soya, blueberry and black raspberry in rat mammary carcinogenesis were found also by other authors .…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Origanum orally administration at the dose of (3 and 30 g/kg). According to results, tumoursuppressive effect of oregano in the breast cancer model has been observed for the first time [38].…”
Section: Anti-cancer Activitymentioning
confidence: 88%